Engineering multi-agent systems : third international workshop, EMAS 2015, Istanbul, Turkey, May 5, 2015, revised, selected, and invited papers /: third international workshop, EMAS 2015, Istanbul, Turkey, May 5, 2015, revised, selected, and invited papers. (2015) - Unknown
No abstract available